Acid-treated graphitic mesoporous carbon for adsorption of basic red 2 dye in aqueous solution - Endud, Salasiah (2014)
A graphitic mesoporous carbon-based material (GMC) was prepared by a nano-casting process. SBA-15 was used as a hard template and sucrose as a carbon precursor in this procedure. To generate surface functionalities, GMC was treated with nitric acid. The acid-treated GMC material was then used as an adsorbent for Basic Red 2 dye (BR2) in aqueous solutions. The morphology, pore structure and surface functional groups of GMC samples were analyzed by field emission scanning electron microscopy (FESEM), Brunauer-Emmett-Teller method (BET), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and Boehm titration. Nitrogen adsorption-desorption analysis revealed a type IV isotherm characteristic of mesoporous materials with BET surface area of approximately 1000 m2g-1 and pore volume of 0.9 cm3g-1. The effects of different adsorption parameters such as initial dye solution pH, initial dye solution concentration and temperature on BR2 uptake were investigated. Surface area of BET and pore volume were decreased after the treatment but the adsorption capacity of BR2 increased to its optimum value in initial dye solution concentration of 200 mgL-1 and pH of 10 at 60 °C.